Estimating Inhaled Corticosteroid Exposure from Short-Acting β2-Agonist–Inhaled Corticosteroid Rescue - Lugogo N; Gilbert I; Pollack M; Gandhi H; Tkacz J; Lanz MJ (Journal of Asthma and Allergy, 2023)
Njira Lugogo,1 Ileen Gilbert,2 Michael Pollack,2 Hitesh Gandhi,2 Joseph Tkacz,3 Miguel J Lanz4 1Department of Medicine, Division of Pulmonary and Critical Care Medicine, University of Michigan, Ann Arbor, MI, USA; 2BioPharmaceuticals Medical, AstraZeneca, Wilmington, DE, USA; 3Inovalon, Bowie, MD, USA; 4Allergy and Asthma, AAADRS Clinical Research Center, Coral Gables, FL, USACorrespondence: Michael Pollack, BioPharmaceuticals Medical, AstraZeneca, 1800 Concord Pike, Wilmington, DE, 19850, USA, Tel +1-302-886-1253, Email Michael.pollack1@astrazeneca.com